Uno sguardo sensibile. Il detective e i procedimenti della conoscenza mediologica - Antonio Rafele (Firenze University Press, 2021)
This paper aims to realize a contribution of social theory, with a focus on the relationships between experience, emotions and knowledge in the context of the metropolis and the media. It proposes an inquiry of the detective and the mediological reflection as a problematic constellation through the following conceptual steps: a) the reciprocal relationship between phenomenon, shock and images; b) the relationship between fragment and organic constellation of thought; c) the central value assumed by detail and circumstances; d) the interdependence between the sphere of feeling, immersion and states of consciousness.